Understanding A/S Level Government and Politics : A guide for A/S level politics students - Wilson, Chris (Manchester : Manchester University Press, 2003)
This is the first textbook to cover the A/S-level government and politics syllabuses offered by the main examination boards. Clearly written, and with further sources of information, in written form and on the Web, this is the perfect information source for students preparing for the A/S-level politics exam.
Includes bibliographical references and index.
Keywords: Political science; Politics and Government; Great Britain -- Politics and government -- 1997-